The Promise of Grassroots Approaches to Solving Absenteeism in Primary Health-Care Facilities in Nigeria: Evidence from a Qualitative Study - Obinna Onwujekwe; Prince Agwu; Pallavi Roy; Eleanor Hutchinson; Charles Orjiakor; Martin McKee; Aloysius Odii; Chukwudi Nwokolo; Mushtaq Khan; Susannah Mayhew; Dina Balabanova (Taylor & Francis Group, 2023)
ABSTRACTAbsenteeism among primary health-care (PHC) workers in Nigeria is widespread and is a major obstacle to achieving Universal Health Coverage (UHC). There is increasing research on the forms it takes and what drives them, but limited evidence on how to address it. The dominant approach has involved government-led topdown solutions (vertical approach). However, these have rarely been successful in countries such as Nigeria. This paper explores alternative approaches based on grassroots (horizontal) approaches. Data collected from interviews with 40 PHC stakeholders in Enugu, Nigeria, were organized in thematic clusters that explored the contribution of horizontal interventions to solving absenteeism in primary health-care facilities. We applied phenomenology to analyze the lived (practical) experiences of respondents. Absenteeism by PHC workers was prevalent and is encouraged by the complex configuration of the PHC system and its operating environment, which constrains topdown interventions. We identified several horizontal approaches that may create effective incentives and compulsions to reduce absenteeism, which include leveraging community resources to improve security of facilities, tapping the resources of philanthropic individuals and organizations to provide accommodation for health workers, and engaging trained health workers as volunteers or placeholders to address shortages of health-care staff. Nevertheless, a holistic response to absenteeism must complement horizontal approaches with vertical measures, with the government supporting and encouraging the health system to develop self-enforcing mechanisms to tackle absenteeism.